Electrolyte for lithium-sulfur secondary battery and lithium-sulfur secondary battery
Patent Information
- Application Number
- JP2020187052
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-10
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-11-10
AI Technical Summary
【0031】 本発明の一態様によれば、孔径が2nm以上の細孔を含む多孔性炭素と、硫黄との複合材料を正極用材料として用いた場合であっても、当該複合材料からのリチウムポリスルフィドの溶出を効果的に抑制することができる。また、本発明の一態様によれば、優れた充放電特性を有するリチウム-硫黄系二次電池を提供することができる。
Smart Images

Figure 0007630154000006 
Figure 0007630154000007 
Figure 0007630154000008
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolyte for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery. [Background technology]
[0002] Lithium ion secondary batteries are secondary batteries that have excellent performance, such as high energy density, the ability to operate under high voltage, and a long life due to low self-discharge. In recent years, there has been a demand for even higher energy density in order to promote the further spread of electric vehicles and the like.
[0003] However, because lithium ion secondary batteries use cobalt, manganese, nickel, and the like, there are resource and price constraints on achieving high energy density.
[0004] Lithium-sulfur secondary batteries using sulfur in the positive electrode can obtain a discharge capacity much larger than that of lithium-ion secondary batteries. In addition, sulfur is an abundant resource, so it is cheaper and easier to obtain than the cobalt, manganese, nickel, etc. Therefore, lithium-sulfur secondary batteries are attracting attention as the next generation of secondary batteries.
[0005] On the other hand, sulfur is an insulator that does not have electronic conductivity. Therefore, a method of compounding sulfur with an electronic conductive material has been proposed. In Non-Patent Document 1, carbon nanotubes, graphene, porous carbon, conductive polymers, polyacrylonitrile, metal oxides, etc. are proposed as examples of the electronic conductive material. An example of using the electronic conductive material is an electrode material in which sulfur is adsorbed into the nanoporosity of porous carbon, as disclosed in Patent Document 1.
[0006] Patent Document 2 discloses a binder for use in electrodes of lithium-sulfur secondary batteries, and also discloses the use of a composite of sulfur and porous carbon as a positive electrode material.
[0007] On the other hand, in lithium-sulfur secondary batteries, when they are discharged, lithium metal is oxidized at the negative electrode, and lithium ions dissolve in the electrolyte. The lithium ions react with sulfur at the positive electrode, and are reduced to lithium sulfide (Li2S) via the intermediate product lithium polysulfide.
[0008] However, the lithium polysulfide is easily dissolved in the electrolyte, causing self-discharge due to the so-called redox shuttle, leading to rapid capacity loss and a decrease in the charge / discharge efficiency of the lithium-sulfur secondary battery.
[0009] Patent Document 3 discloses an electrolyte solution for a lithium-sulfur secondary battery that uses a composite of sulfur and porous carbon as a positive electrode material, the electrolyte solution containing a fluorinated ether, as a technology for suppressing the elution of lithium polysulfide. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2013-118191 A [Patent Document 2] JP 2016-100094 A [Patent Document 3] International Publication No. 2018 / 163778 [Non-patent literature]
[0011] [Non-Patent Document 1] X. Ji, KT Lee and LF Nazar, “A highly ordered nanostructured carbon-sulfur cathode for lithium-sulfur batteries”, Nature Materials. 8 (2009) 500. Summary of the Invention [Problem to be solved by the invention]
[0012] Here, when a composite material of porous carbon and sulfur is used as a positive electrode material, it is preferable that the amount of sulfur supported in the porous carbon is larger, since the energy density of the lithium-sulfur secondary battery can be increased. From the viewpoint of supporting a large amount of sulfur, it is preferable that the pore size of the porous carbon is larger.
[0013] However, the present inventors have found that when ethylene carbonate is used as a solvent for an electrolyte in a lithium-sulfur secondary battery in which the composite is used as a positive electrode material and the porous carbon has pores of 2 nm or more, a problem occurs in that charge / discharge characteristics cannot be obtained. Ethylene carbonate is a solvent for electrolytes commonly used in lithium ion secondary batteries.
[0014] Although Patent Document 1 and Non-Patent Document 1 refer to the composite material, they make no mention whatsoever of the problem between the electrolyte and the charge / discharge characteristics, and therefore cannot solve the problem.
[0015] Patent Document 2 merely discloses the use of microporous carbon as the porous carbon and the use of ethylene carbonate as a preferred solvent for the electrolyte. Patent Document 2 does not recognize any problems that may arise when the porous carbon has pores of 2 nm or more, and therefore cannot solve the problems.
[0016] Patent Document 3 discloses that the electrolyte of the lithium-sulfur secondary battery described therein can suppress the formation of Li2S8 among lithium polysulfides. However, as described below, the present inventors have found that the lithium-sulfur secondary battery using the electrolyte has room for improvement in terms of polarization of the charge / discharge characteristics.
[0017] Therefore, an object of one aspect of the present invention is to provide an electrolyte for a lithium-sulfur based secondary battery that can suppress the elution of lithium polysulfide from a composite material of porous carbon containing pores with a pore size of 2 nm or more and sulfur, and can significantly improve the charge / discharge characteristics of the lithium-sulfur based secondary battery. [Means for solving the problem]
[0018] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by using an electrolyte solution containing ethylene carbonate having a chloro group as a solvent, and have thus completed the present invention.
[0019] That is, the present invention includes the following configurations.
[0020] <1> 1. An electrolyte for a lithium-sulfur secondary battery, the lithium-sulfur secondary battery comprising a composite material of porous carbon and sulfur as a positive electrode material, the porous carbon including pores having a pore size of 2 nm or more, and a solvent for the electrolyte including ethylene carbonate having a chloro group.
[0021] <2> The total volume of the pores in the porous carbon is 0.4 cm 3 / g or more 2.0cm 3 / g or less, <1> The electrolyte for a lithium-sulfur secondary battery according to claim 1.
[0022] <3> The total volume of the pores in the porous carbon is 0.9 cm 3 / g or more 2.0cm 3 / g or less, <2> The electrolyte for a lithium-sulfur secondary battery according to claim 1.
[0023] <4> The weight of sulfur supported in the pores of the porous carbon is 30% by weight or more and 90% by weight or less based on the total weight of the porous carbon and the sulfur. <1> ~ <3> 2. The electrolyte for a lithium-sulfur secondary battery according to claim 1 ,
[0024] <5> The weight of sulfur supported in the pores of the porous carbon is 50% by weight or more and 90% by weight or less based on the total weight of the porous carbon and the sulfur. <4> The electrolyte for a lithium-sulfur secondary battery according to claim 1.
[0025] <6> The ratio of the amount of pores having a pore diameter of 2 nm or more to the total amount of pores in the porous carbon is 5% or more and 100% or less. <1> ~ <5> 2. The electrolyte for a lithium-sulfur secondary battery according to claim 1 ,
[0026] <7> The proportion of pores having a pore diameter of 2 nm or more is 40% or more and 100% or less. <6> The electrolyte for a lithium-sulfur secondary battery according to claim 1.
[0027] <8> The content of ethylene carbonate having a chloro group in the solvent is 20% by weight or more and 100% by weight or less. <1> ~ <7> 2. The electrolyte for a lithium-sulfur secondary battery according to claim 1 ,
[0028] <9> The content of ethylene carbonate having a chloro group in the solvent is 30% by weight or more and 100% by weight or less. <8> The electrolyte for a lithium-sulfur secondary battery according to claim 1.
[0029] <10> The solvent includes one or more selected from vinylene carbonate, hydrofluoroether, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and fluoroethylene carbonate; <1> ~ <9> 2. The electrolyte for a lithium-sulfur secondary battery according to claim 1 ,
[0030] <11> <1> ~ <10> 2. A lithium-sulfur secondary battery comprising the electrolyte for a lithium-sulfur secondary battery according to claim 1, wherein a composite material of porous carbon and sulfur is used as a positive electrode material, and the porous carbon contains pores having a pore diameter of 2 nm or more. Effect of the Invention
[0031] According to one aspect of the present invention, even when a composite material of porous carbon containing pores having a pore size of 2 nm or more and sulfur is used as a positive electrode material, it is possible to effectively suppress the elution of lithium polysulfide from the composite material. Also, according to one aspect of the present invention, it is possible to provide a lithium-sulfur secondary battery having excellent charge-discharge characteristics. [Brief description of the drawings]
[0032] [Figure 1] FIG. 1 is a diagram showing the results of a charge-discharge test of the lithium-sulfur secondary batteries prepared in the examples and comparative examples. [Diagram 2] 1 is a graph showing the results of a cycle characteristic test of the lithium-sulfur secondary batteries prepared in the examples and comparative examples. [Diagram 3] 1 is a graph showing the results of a cycle characteristic test of the lithium-sulfur secondary batteries prepared in the examples and comparative examples. [Figure 4] 1 is a graph showing the results of a cycle characteristic test of the lithium-sulfur secondary batteries prepared in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] An embodiment of the present invention will be described in detail below. However, the present invention is not limited to this, and various modifications are possible within the described scope. For example, an embodiment obtained by appropriately combining the technical means disclosed in each of the different embodiments is also included in the technical scope of the present invention. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more, B or less."
[0034] [1. Electrolyte for Lithium-Sulfur Secondary Batteries] An electrolyte for a lithium-sulfur secondary battery according to one embodiment of the present invention is an electrolyte for a lithium-sulfur secondary battery, the lithium-sulfur secondary battery comprising a composite material of porous carbon and sulfur as a positive electrode material, the porous carbon including pores having a pore size of 2 nm or more, and a solvent for the electrolyte including ethylene carbonate having a chloro group.
[0035] (1-1. Positive electrode materials for lithium-sulfur secondary batteries) The lithium-sulfur secondary battery using the electrolyte for lithium-sulfur secondary batteries according to one embodiment of the present invention includes a composite material of porous carbon and sulfur as a positive electrode material. In this specification, the positive electrode material is a material that is applied to or filled in a current collector to prepare a positive electrode, and contains a positive electrode active material, a conductive assistant, a binder, and the like.
[0036] The sulfur is a positive electrode active material. The porous carbon is not particularly limited, but may be preferably an activated carbon obtained by carbonizing a resin, a fossil resource material, or the like, and then activating it with an alkali such as potassium hydroxide. The activated carbon is preferable because it has a large specific surface area and a large pore volume, and has a structure suitable for supporting a large amount of sulfur. In addition, a porous carbon in which the pore structure of carbon is controlled by a template method may also be preferably used. The porous carbon may be one produced based on a known method, or may be a commercially available product.
[0037] The "composite material of porous carbon and sulfur" is a porous carbon in which sulfur is supported in the pores of the porous carbon. That is, the composite material of porous carbon and sulfur also includes porous carbon on which polysulfide is adsorbed. The adsorption may be physical adsorption or chemical adsorption.
[0038] The porous carbon includes pores having a pore diameter of 2 nm or more. The shape of the pores of the porous carbon includes slit-like, wide-open, connected, etc., but the shape is not particularly limited. The types of pores of the porous carbon include micropores having a pore diameter of less than 2 nm, mesopores having a pore diameter of 2 nm or more but less than 50 nm, and macropores having a pore diameter of 50 nm or more.
[0039] As mentioned above, Patent Document 2 discloses the use of microporous carbon as the porous carbon, and the use of ethylene carbonate as a preferred solvent for the electrolyte.
[0040] The microporous carbon disclosed in Patent Document 2 is a porous carbon in which the pores are micropores. In this case, ethylene carbonate cannot enter the micropores, so sulfur supported in the micropores does not dissolve into the electrolyte as lithium polysulfide.
[0041] However, because the diameter of micropores is very small, the amount of sulfur that can be supported is naturally small. Therefore, it is necessary to support sulfur in mesopores, which have a larger diameter than micropores, and to reduce the amount of sulfur that dissolves into the electrolyte.
[0042] The porous carbon contains pores with a pore size of 2 nm or more, and therefore can support more sulfur than porous carbon having only micropores, thereby enabling the lithium-sulfur secondary battery to have a high energy density.
[0043] Moreover, as described later, the electrolyte for a lithium-sulfur secondary battery according to one embodiment of the present invention contains ethylene carbonate having a chloro group as a solvent, and therefore, it is possible to suppress the sulfur from dissolving into the electrolyte as lithium polysulfide. Therefore, the electrolyte for a lithium-sulfur secondary battery according to one embodiment of the present invention can provide a lithium-sulfur secondary battery having excellent charge and discharge characteristics.
[0044] The total volume of the pores in the porous carbon is 0.4 cm from the viewpoint of supporting a large amount of sulfur. 3 / g~2.0cm 3 / g, and preferably 0.9 cm 3 / g~2.0cm 3 / g, more preferably 1.2 cm 3 / g~2.0cm 3 It is more preferable that the molecular weight is / g.
[0045] When the total volume of the pores of the porous carbon is within the above range, sulfur can be sufficiently supported in the porous carbon, thereby further improving the energy density of the lithium-sulfur secondary battery.
[0046] The pore volume can be measured, for example, by using AUTOSORB iQ manufactured by Quantachrome Corporation.
[0047] Furthermore, the weight of sulfur supported in the pores of the porous carbon is preferably 30% by weight or more and 90% by weight or less, more preferably 50% by weight or more and 90% by weight or less, and even more preferably 70% by weight or more and 90% by weight or less, based on the total weight of the porous carbon and the weight of the sulfur.
[0048] In one embodiment of the present invention, the weight of the sulfur supported in the pores of the porous carbon may be 70% by weight or less with respect to the total weight of the porous carbon and the weight of the sulfur.
[0049] When the weight of the sulfur is within the above range, the amount of sulfur supported in the porous carbon can be sufficiently increased, and the charge / discharge characteristics of the lithium-sulfur secondary battery can be improved. The more the amount of sulfur supported, the more preferable it is, but in consideration of the supporting capacity of the porous carbon, the upper limit is about 90% by weight. The amount of sulfur supported can be confirmed by the method described later in the Examples.
[0050] The ratio of the amount of pores having a pore diameter of 2 nm or more to the total amount of pores in the porous carbon is preferably 5% or more, more preferably 20% or more, and particularly preferably 40% or more. The higher the ratio of the amount of pores having a pore diameter of 2 nm or more, the more preferable, and the ratio is preferably 40% or less than 20% or less, more preferably 60% or less, even more preferably 80% or less, and particularly preferably 100% or less to the total amount of pores in the porous carbon.
[0051] In this specification, the "amount of pores" may mean either the number of pores or the volume of the pores. That is, the ratio of the amount of pores having a pore diameter of 2 nm or more to the total amount of pores in the porous carbon may be the ratio of the number of pores having a pore diameter of 2 nm or more to the total number of pores in the porous carbon. Alternatively, the ratio of the amount of pores having a pore diameter of 2 nm or more to the total amount of pores in the porous carbon may be the ratio of the volume of pores having a pore diameter of 2 nm or more to the total volume of pores in the porous carbon.
[0052] When the ratio is 5% or more, the amount of sulfur supported can be increased more than in porous carbon having only micropores, making it easier to provide a lithium-sulfur secondary battery with a high energy density.
[0053] In addition, when the ratio of macropores to the pores is high, the density of the electrode tends to decrease, so it is more preferable that the pores having a pore size of 2 nm or more are mesopores.
[0054] The ratio of the number of pores having a pore diameter of 2 nm or more and the pore diameter of the pores can be confirmed by measuring the specific surface area of the porous carbon by the BET method and measuring the pore distribution and pore volume by the quenched solid phase density function method (QSDFT). Quantachrome's AUTOSORB iQ can be used as a measuring device.
[0055] The specific surface area, pore distribution, and pore volume of the porous carbon can be measured by measuring the nitrogen adsorption isotherm at liquid nitrogen temperature for a sample that has been degassed in vacuum at 200° C. for 3 hours.
[0056] The volume ratio of pores having a pore diameter of 2 nm or more can be confirmed from a pore distribution diagram obtained from the above-mentioned AUTOSORB iQ.
[0057] The loading of sulfur into the pores can be carried out, for example, by mixing the porous carbon and sulfur in a mortar or the like, and then heating the resulting mixture in a muffle furnace or the like. As the sulfur, commercially available sulfur flowers or the like can be used.
[0058] In the present specification, the form of sulfur is not particularly limited. For example, one or more sulfurs selected from the group consisting of α-sulfur (orthorhombic sulfur), β-sulfur (monoclinic sulfur), γ-sulfur (monoclinic sulfur), rubber sulfur, and plastic sulfur can be used.
[0059] The specific surface area of the porous carbon is set to 750 m from the viewpoint of supporting a large amount of sulfur. 2 / g~3300m 2 / g, and 1200m 2 / g~3300m 2 It is more preferable that the molecular weight is / g.
[0060] The conductive assistant, which is the material for the positive electrode, can be any electronically conductive material that does not adversely affect the battery performance. Carbon black such as acetylene black and ketjen black is usually used as the conductive assistant, but other conductive assistants may be used. For example, conductive materials such as natural graphite (scale graphite, flake graphite, earthy graphite, etc.), artificial graphite, carbon whiskers, carbon fiber powder, metal (copper, nickel, aluminum, silver, gold, etc.) powder, metal fiber, conductive ceramic material, carbon nanotube, etc. may be used. These may be used alone or as a mixture of two or more kinds.
[0061] Moreover, as the binder, for example, an aqueous binder can be used. The aqueous binder is not particularly limited as long as it can bind the composite material of the porous carbon and sulfur with the conductive assistant, etc. For example, one or more binders selected from the group consisting of styrene-butadiene rubber (SBR) as a rubber binder, carboxymethyl cellulose (CMC) as a dispersant, alginate as an aqueous binder, polyglutamate, etc. can be used.
[0062] The positive electrode material can be prepared, for example, by homogeneously mixing the sulfur-loaded porous carbon, the conductive additive, and the binder. Examples of the mixing method include a method in which the sulfur-loaded porous carbon and the conductive additive are mixed in a mortar or the like, and the resulting mixture is further stirred using a rotation-revolution mixer.
[0063] (1-2. Electrolyte for lithium-sulfur secondary batteries) An electrolyte solution for a lithium-sulfur secondary battery (hereinafter also simply referred to as an electrolyte solution) contains a solvent and an electrolyte containing lithium.
[0064] The electrolyte solvent for the lithium-sulfur secondary battery (hereinafter also simply referred to as electrolyte solvent) contains ethylene carbonate having a chloro group. The number of chloro groups in the ethylene carbonate having a chloro group is not particularly limited, and may be 1 to 4.
[0065] The bonding position of the chloro group to the ethylene carbonate is not particularly limited and may be present at any position. That is, for example, all carbons in ethylene carbonate may have one or two chloro groups, or only one carbon may have a chloro group. Also, the chloro group may not be bonded directly to the carbon of ethylene carbonate, but may be bonded to the carbon as a chloromethylene group, for example.
[0066] Examples of ethylene carbonate having a chloro group include chloroethylene carbonate (4-chloro-1,3-dioxolan-2-one), 3-chloropropylene carbonate, 4,4,5,5-tetrachloro-1,3-dioxolan-2-one, etc. The electrolyte may contain only one type of ethylene carbonate containing a chloro group, or two or more types of ethylene carbonates.
[0067] By including ethylene carbonate having a chloro group in the solvent of the electrolyte, even if the composite material of porous carbon and sulfur contains pores having a pore size of 2 nm or more, it is possible to prevent sulfur from eluting from the pores into the electrolyte as lithium polysulfide.
[0068] As shown in Example 1 described later, when an electrolyte solution containing ethylene carbonate having a chloro group as a solvent was used, a charge / discharge curve was obtained that is considered to indicate that a coating was formed in the pores of the composite material (sulfur-loaded activated carbon).
[0069] From this, it is considered that, in the electrolyte for a lithium-sulfur secondary battery according to one embodiment of the present invention, first, ethylene carbonate having a chloro group forms a coating on the pores. Next, it is considered that the coating suppresses contact between the sulfur and the electrolyte and suppresses the elution of lithium polysulfide from the pores. As a result, it is considered that the loss of sulfur contained in the composite material is prevented and sulfur can be effectively used as a positive electrode active material, thereby providing excellent charge and discharge characteristics to the lithium-sulfur secondary battery.
[0070] In addition, in the examples described later, it has been shown that the use of ethylene carbonate having a chloro group as the solvent can provide a lithium-sulfur secondary battery with better charge-discharge characteristics than the use of fluoroethylene carbonate as the solvent.
[0071] The content of the ethylene carbonate having a chloro group in the solvent of the electrolytic solution is preferably 20% by weight or more and 100% by weight or less, more preferably 30% by weight or more and 100% by weight or less, and even more preferably 50% by weight or more and 100% by weight or less, when the weight of the solvent is 100% by weight.
[0072] When the content is 20% by weight or more, the coating can be formed to a degree that can sufficiently suppress the elution of lithium polysulfide when used as a solvent for the electrolyte, which is preferable in terms of improving the discharge capacity of a lithium-sulfur secondary battery.
[0073] The solvent of the electrolytic solution may contain a solvent other than ethylene carbonate having a chloro group as a co-solvent, such as one or more selected from the group consisting of carbonates other than ethylene carbonate, ethers, sulfur compounds, halogenated hydrocarbons, phosphate ester compounds, sulfolane hydrocarbons, and ionic liquids.
[0074] The carbonates other than ethylene carbonate are preferably cyclic carbonates such as fluoroethylene carbonate (FEC) and vinylene carbonate (VC); and chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC).
[0075] The ethers are preferably cyclic ethers such as dioxolane (DOL) and tetrahydrofuran; or chain ethers such as dimethoxyethane (DME), triglyme (G3), tetraglyme (G4), and hydrofluoroethers.
[0076] Among the co-solvents, one or more selected from vinylene carbonate, hydrofluoroether, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and fluoroethylene carbonate are particularly preferred from the viewpoint of improving the charge / discharge characteristics of the lithium-sulfur secondary battery.
[0077] An example of the hydrofluoroether is 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)-propane.
[0078] Examples of the lithium-containing electrolyte include LiPF6, LiBF4, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI). Among them, LiPF6, LiFSI, and LiTFSI are preferred, and LiTFSI is more preferred. The lithium-containing electrolyte may be used alone or in combination of two or more.
[0079] [2. Lithium-sulfur secondary batteries] A lithium-sulfur secondary battery according to an embodiment of the present invention includes an electrolyte for a lithium-sulfur secondary battery according to an embodiment of the present invention, and uses a composite material of porous carbon and sulfur as a positive electrode material, and the porous carbon includes pores having a pore diameter of 2 nm or more.
[0080] According to this configuration, as shown in the examples described later, the amount of sulfur supported in the pores of the porous carbon contained in the positive electrode material can be increased, and the sulfur can be prevented from being eluted as lithium polysulfide by the electrolyte solution, so that a lithium-sulfur secondary battery exhibiting a high discharge capacity can be provided.
[0081] The electrolyte and the sulfur-supported porous carbon are as described above. The electrolyte can be prepared, for example, by mixing an electrolyte containing lithium with a solvent.
[0082] The lithium-sulfur secondary battery according to one embodiment of the present invention can be manufactured by assembling the positive electrode, the negative electrode, the electrolyte for the lithium-sulfur secondary battery according to one embodiment of the present invention, a separator, a case, and the like, by a conventionally known method.
[0083] The positive electrode can be prepared, for example, by applying or filling a positive electrode slurry onto a current collector, drying the slurry, and then pressure-molding the slurry, followed by vacuum drying.
[0084] The positive electrode slurry can be prepared, for example, by adding a conductive assistant to a binder solution prepared by dissolving the binder in pure water, and then adding and mixing the composite material of porous carbon and sulfur.
[0085] The weight ratio of the composite material, the conductive assistant, and the binder in the positive electrode slurry is preferably 80:10:10 to 97:0:3, and more preferably 85:5:10 to 95:0:5, from the viewpoint of uniformly applying or filling the current collector.
[0086] As the current collector, any electronic conductor that does not adversely affect the constructed battery can be used. Examples include aluminum, titanium, stainless steel, nickel, baked carbon, conductive polymers, conductive glass, etc. For the purpose of improving adhesion, conductivity, oxidation resistance, etc., a current collector whose surface is treated with carbon, nickel, titanium, silver, etc. may be used.
[0087] The shape of the current collector may be any of foil, film, sheet, net, etc. Among them, a current collector having a three-dimensional structure such as a honeycomb structure is preferable because it can be filled with more positive electrode material for the lithium-sulfur secondary battery and can have a large capacity. As the current collector, for example, a 3D aluminum current collector can be mentioned.
[0088] The negative electrode can be prepared, for example, by applying or filling a negative electrode slurry onto a current collector, drying the slurry, and then pressure-molding the slurry, followed by vacuum drying.
[0089] The negative electrode slurry can be prepared, for example, by adding a conductive assistant to a binder solution prepared by dissolving a binder in pure water, and then adding and mixing a negative electrode active material. For example, metallic lithium can be used as the negative electrode active material.
[0090] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES
[0091] <Charge / discharge test> A constant current charge / discharge test was performed using a BTS2400W (manufactured by Nagano Co., Ltd.) with the positive electrode of the lithium-sulfur secondary battery prepared in the examples and comparative examples described below as the working electrode. The charging mode was the CC method ("CC" is an abbreviation for constant current), and the discharging mode was the CC mode. The set current density was 167.2mA / g (a current density of 1672mA / g is defined as 1C. Hereinafter, 167.2mA / g will be referred to as 0.1C). The cutoff voltage had a lower limit of 1.0V and an upper limit of 3.0V. The test was performed in an environment of 25°C.
[0092] The charge capacity and discharge capacity are based on the weight of sulfur and are expressed in units of mA·h (g sulfur). -1 It was defined as follows.
[0093] <Cycle characteristic test> The charge / discharge rate was set to 0.1 / 0.1 C, and the charge / discharge cycles were 1 to 100. The higher the discharge capacity at each cycle, the better the lithium-sulfur secondary battery.
[0094] The coulombic efficiency and capacity retention rate were calculated by the following formulas. Coulombic efficiency (%) = (Coulombic efficiency at 100th cycle / Coulombic efficiency at 2nd cycle) x 100 Capacity retention rate (%) = (100th cycle discharge capacity / 2nd cycle discharge capacity) x 100 Example 1 (Preparation of sulfur-loaded activated carbon) Activated carbon having mesopores with a pore size of 2 nm to 4 nm and sulfur flowers (manufactured by Wako Pure Chemical Co., Ltd., purity over 99%) were mixed in an agate mortar to obtain a mixture with a weight ratio of 35:65. The mixture was transferred to a heat-resistant metal container, which was then placed in a muffle furnace and subjected to a heat treatment in the air.
[0095] The volume of the pores in the activated carbon is 1.6 cm 3 / g, and the specific surface area is 1307m 2 The ratio of the number of macropores, mesopores, and micropores in the activated carbon was 0:40:60.
[0096] Specifically, after the metal container was placed in a furnace, the temperature inside the furnace was raised to 155°C and maintained at this temperature for 5 hours to melt the sulfur. The sulfur was adsorbed into the pores of the activated carbon by capillary action. Thereafter, the furnace was sufficiently air-cooled to room temperature, and the metal container was removed from the furnace to obtain activated carbon carrying sulfur. This activated carbon corresponds to the "composite material of porous carbon and sulfur" in one embodiment of the present invention.
[0097] The amount of sulfur supported in the activated carbon (weight of sulfur supported in the pores of the porous carbon) was measured by the following method. That is, the activated carbon supporting sulfur was placed in an alumina cell, and thermogravimetric analysis (TGA) was performed using a Shimadzu DTG-60AH. The measurement was performed under the conditions of measurement gas Ar, gas flow rate 50 ml / min, temperature rise rate 5°C / min, and upper limit temperature 600°C. The amount of sulfur supported was 65% by weight based on the total weight of the activated carbon supporting sulfur.
[0098] (Preparation of binder solution) As a binder, styrene-butadiene rubber (SBR), a rubber-based binder, and carboxyl methyl cellulose (CMC), a dispersant, were dissolved in pure water to prepare a binder solution with a CMC concentration of 1 to 2 wt%.
[0099] (Preparation of slurry for positive electrodes of lithium-sulfur secondary batteries) The conductive additive acetylene black was added to the binder solution, and then the sulfur-loaded activated carbon was added to prepare a positive electrode slurry. The weight ratio of the sulfur-loaded activated carbon, acetylene black, dispersant (CMC), and binder (SBR) was 90:5:3:2.
[0100] (Preparation of positive electrodes for lithium-sulfur secondary batteries) A two-electrode flat cell positive electrode was fabricated as a positive electrode for lithium-sulfur secondary batteries.
[0101] The positive electrode for the two-electrode flat cell was prepared by the following method. First, the positive electrode slurry was mixed with the activated carbon carrying sulfur so that the weight of the activated carbon was 1.3 mg / cm2 per unit area of the current collector. 2 The mixture was applied to an aluminum foil (current collector) so that the resultant mixture was uniformly mixed, and the mixture was dried at 40° C. for 1 hour in an oven under atmospheric pressure. The dried current collector was then rolled using a roll press machine, and punched out to a size with a diameter of 12 mm to obtain a molded body. The molded body was further vacuum-dried for 12 hours in a bell jar at 50° C. to produce a positive electrode for a two-electrode flat cell.
[0102] (Preparation of negative electrodes for lithium-sulfur secondary batteries) A two-electrode flat cell anode was fabricated as a lithium-sulfur secondary battery anode.
[0103] The negative electrode for the two-electrode flat cell was prepared by punching out a lithium foil with a thickness of 20 μm to a diameter of 16 mm in an air atmosphere with a dew point of −40° C. or lower.
[0104] (Preparation of electrolyte for lithium-sulfur secondary battery) Lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as LiTFSI) was used as the lithium-containing electrolyte, and a mixed solvent of 4-chloro-1,3-dioxolane-2-one (chloroethylene carbonate) (hereinafter referred to as ClEC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)-propane (hereinafter referred to as HFE) in a volume ratio of 50:50 was used as the non-aqueous solvent.
[0105] The method for preparing the electrolyte solution will be described in more detail. ClEC and HFE were mixed in a volume ratio of 50:50 to prepare a mixed solvent. LiTFSI was then dissolved in the mixed solvent to obtain a LiTFSI / ClEC:HFE ratio of 1.0 mol / L to prepare an electrolyte solution for a lithium-sulfur secondary battery.
[0106] (Fabrication of lithium-sulfur secondary batteries) In an air atmosphere with a dew point of −40° C. or lower, a lithium-sulfur secondary battery was produced by the following procedure using the positive electrode produced by the above (Preparation of positive electrode for lithium-sulfur secondary battery), the negative electrode produced by the above (Preparation of negative electrode for lithium-sulfur secondary battery), the electrolyte prepared by the above (Preparation of electrolyte for lithium-sulfur secondary battery), and a polypropylene microporous film as a separator.
[0107] A two-electrode flat cell (coated electrodes) was used as the cell for the lithium-sulfur secondary battery. First, a positive electrode, a separator, and a negative electrode were stacked in this order in the cell. Next, the electrolyte was injected into the cell to prepare a lithium-sulfur secondary battery.
[0108] The lithium-sulfur secondary battery was subjected to the above-mentioned charge / discharge test and cycle characteristic test.
[0109] Example 2 (Preparation of sulfur-loaded activated carbon) Activated carbon carrying sulfur was obtained in the same manner as in Example 1, except that the activated carbon had mesopores with a pore size of 2 nm or more and 3 nm or less.
[0110] The volume of the pores in the activated carbon is 1.3 cm 3 / g, and the specific surface area is 2924m 2 / g. The ratio of the number of macropores:mesopores:micropores in the pores of the activated carbon was 0:5:95.
[0111] The amount of sulfur supported on the activated carbon was measured by the same method as in Example 1. The amount of sulfur supported was 61% by weight based on the total weight of the activated carbon supporting sulfur.
[0112] (Preparation of binder solution) As the binder, polyglutamate, which is a water-based binder, was dissolved in pure water to prepare a binder solution with a polyglutamate concentration of 5 wt %.
[0113] (Preparation of slurry for positive electrodes of lithium-sulfur secondary batteries) The carbon nanotubes, which are a conductive additive, and the activated carbon carrying sulfur were then added to the binder solution to prepare a positive electrode slurry. The weight ratio of the activated carbon carrying sulfur, the carbon nanotubes, and the binder was 94:1:5.
[0114] (Fabrication of lithium-sulfur secondary batteries) The weight of the sulfur-supported activated carbon per unit area of the current collector is 1.1 to 1.3 mg / cm 2 A positive electrode for a two-electrode flat cell was produced in the same manner as in Example 1, except that an aluminum foil (current collector) was coated with the above-mentioned solution.
[0115] Other than that, a lithium-sulfur secondary battery was fabricated in the same manner as in Example 1.
[0116] Example 3 A lithium-sulfur secondary battery was produced in the same manner as in Example 2, except that the electrolyte solution was prepared as follows.
[0117] ClEC and 4-fluoro-1,3-dioxolane-2-one (fluoroethylene carbonate) (hereinafter referred to as FEC) were mixed in a volume ratio of 50:50 to prepare a mixed solvent. LiTFSI was then dissolved in the mixed solvent to give a LiTFSI / ClEC:FEC ratio of 1.0 mol / L to prepare a solution for use as an electrolyte for a lithium-sulfur secondary battery.
[0118] Example 4 A lithium-sulfur secondary battery was produced in the same manner as in Example 2, except that the electrolyte solution was prepared as follows.
[0119] ClEC and the VC were mixed in a volume ratio of 50:50 to prepare a mixed solvent. LiTFSI was then dissolved in the mixed solvent to give a LiTFSI / ClEC:VC ratio of 1.0 mol / L to prepare a solution for use as an electrolyte for a lithium-sulfur secondary battery.
[0120] The amount of sulfur supported in the sulfur-supported activated carbon was 66% by weight based on the total weight of the sulfur-supported activated carbon.
[0121] Example 5 A lithium-sulfur secondary battery was produced in the same manner as in Example 2, except that the electrolyte solution was prepared as follows.
[0122] LiTFSI was dissolved in ClEC so that the LiTFSI / ClEC ratio was 1.0 mol / L, and the resulting solution was used as the electrolyte for the lithium-sulfur secondary battery.
[0123] The amount of sulfur supported in the sulfur-supported activated carbon was 63% by weight based on the total weight of the sulfur-supported activated carbon.
[0124] Example 6 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 2, except that the electrolyte solution was prepared as follows.
[0125] A solution was prepared by dissolving LiTFSI in ClEC to give a LiTFSI / ClEC ratio of 1.0 mol / L. Next, 10% by volume of vinylene carbonate (VC) was added to the 100% by volume solution to prepare an electrolyte for a lithium-sulfur secondary battery.
[0126] The amount of sulfur supported in the sulfur-supported activated carbon was 66% by weight based on the total weight of the sulfur-supported activated carbon.
[0127] Example 7 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 2, except that the electrolyte solution was prepared as follows.
[0128] ClEC and HFE were mixed in a volume ratio of 90:10 to prepare a mixed solvent. LiTFSI was then dissolved in the mixed solvent to prepare a solution of 1.0 mol / L LiTFSI / ClEC:HFE. VC was then added at 10 volume% to the 100 volume% solution to prepare an electrolyte for a lithium-sulfur secondary battery.
[0129] The amount of sulfur supported in the sulfur-supported activated carbon was 66% by weight based on the total weight of the sulfur-supported activated carbon.
[0130] Example 8 ClEC and HFE were mixed in a volume ratio of 70:30 to prepare a mixed solvent. Next, LiTFSI was dissolved in the mixed solvent to prepare a solution of 1.0 mol / L LiTFSI / ClEC:HFE. Furthermore, 10 volume % of VC was added to the 100 volume % solution to prepare an electrolyte for a lithium-sulfur secondary battery. A lithium-sulfur secondary battery was prepared in the same manner as in Example 7 in other respects.
[0131] The amount of sulfur supported in the sulfur-supported activated carbon was 66% by weight based on the total weight of the sulfur-supported activated carbon.
[0132] Example 9 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 7, except that ClEC and HFE were mixed in a volume ratio of 50:50 to form a mixed solvent.
[0133] The amount of sulfur supported in the sulfur-supported activated carbon was 63% by weight based on the total weight of the sulfur-supported activated carbon.
[0134] Example 10 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 7, except that ClEC and HFE were mixed in a volume ratio of 30:70 to form a mixed solvent.
[0135] The amount of sulfur supported in the sulfur-supported activated carbon was 63% by weight based on the total weight of the sulfur-supported activated carbon.
[0136] Example 11 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 2, except that the electrolyte, positive electrode, negative electrode, and electrolyte were prepared as follows. The amount of sulfur supported in the sulfur-supported activated carbon was 66% by weight based on the total weight of the sulfur-supported activated carbon.
[0137] A positive electrode for a laminate cell was prepared by the following method.
[0138] First, a positive electrode slurry prepared in the same manner as in Example 1 was mixed with the activated carbon having a weight of 11 mg / cm2 per unit area of the current collector. 2 More than 13mg / cm 2The mixture was filled into a 3D aluminum current collector (Celmet, manufactured by Sumitomo Electric Industries, Ltd.) as follows. Next, the 3D aluminum current collector was dried at 40° C. for 1 hour using an oven under atmospheric pressure. The dried current collector was then rolled using a roll press machine and cut to a size of 24 mm x 24 mm using scissors to obtain a molded body. The molded body was further vacuum dried for 12 hours using a bell jar at 50° C. to produce a positive electrode for a laminate cell.
[0139] The negative electrode for the laminate cell was prepared by cutting a lithium foil having a thickness of 30 μm into a size of 30 mm×35 mm using scissors in an air atmosphere with a dew point of −40° C. or lower.
[0140] The electrolyte for the lithium-sulfur secondary battery was prepared in the same manner as in Example 6.
[0141] Example 12 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that ClEC and HFE were mixed in a volume ratio of 90:10 to prepare a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 66 wt % based on the total weight of the sulfur-supported activated carbon.
[0142] Example 13 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that ClEC and HFE were mixed in a volume ratio of 70:30 to prepare a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 64 wt % based on the total weight of the sulfur-supported activated carbon.
[0143] Example 14 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that ClEC and HFE were mixed in a volume ratio of 50:50 to prepare a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 65 wt % based on the total weight of the sulfur-supported activated carbon.
[0144] Example 15 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that in the preparation of the electrolyte, ClEC and dimethyl carbonate (hereinafter referred to as DMC) were mixed in a volume ratio of 70:30 to form a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 67% by weight, based on the total weight of the sulfur-supported activated carbon.
[0145] Example 16 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that in the preparation of the electrolyte, ClEC and DMC were mixed in a volume ratio of 50:50 to prepare a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 64 wt % based on the total weight of the sulfur-supported activated carbon.
[0146] Example 17 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that in the preparation of the electrolyte, ClEC and ethyl methyl carbonate (hereinafter referred to as EMC) were mixed in a volume ratio of 70:30 to form a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 65% by weight, based on the total weight of the sulfur-supported activated carbon.
[0147] Example 18 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that in the preparation of the electrolyte, ClEC and diethyl carbonate (hereinafter referred to as DEC) were mixed in a volume ratio of 70:30 to prepare a mixed solvent. The amount of sulfur supported in the sulfur-supported activated carbon was 67% by weight, based on the total weight of the sulfur-supported activated carbon.
[0148] Comparative Example 1 In preparing the electrolyte solution, lithium hexafluorophosphate (hereinafter referred to as LiPF6) was used as the lithium-containing electrolyte, and a mixed solvent (commercially available from Kishida Chemical Co., Ltd.) in which ethylene carbonate (hereinafter referred to as EC) and DMC were mixed in a volume ratio of 50:50 was used as the non-aqueous solvent.
[0149] Other than that, a lithium-sulfur secondary battery was fabricated in the same manner as in Example 1.
[0150] Comparative Example 2 A lithium-sulfur secondary battery was produced in the same manner as in Example 1, except that in preparing the electrolyte solution, FEC was used instead of ClEC as the non-aqueous solvent.
[0151] Comparative Example 3 A lithium-sulfur secondary battery was produced in the same manner as in Example 2, except that in preparing the electrolyte, a mixed solvent of EC and DMC in a volume ratio of 50:50 (a commercially available product manufactured by Kishida Chemical Co., Ltd.) was used as the non-aqueous solvent.
[0152] Comparative Example 4 A lithium-sulfur secondary battery was produced in the same manner as in Example 2, except that in preparing the electrolyte solution, a mixed solvent of FEC and HFE in a volume ratio of 50:50 was used as the non-aqueous solvent.
[0153] Comparative Example 5 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that the electrolyte solution was prepared as follows.
[0154] In the electrolyte, LiPF6 was used as the lithium-containing electrolyte. In addition, a mixed solvent (commercially available from Kishida Chemical Co., Ltd.) in which EC and DMC were mixed in a volume ratio of 50:50 was used as the non-aqueous solvent. Next, a solution was prepared by dissolving LiPF6 in the mixed solvent to a ratio of 1.0 mol / L LiPF6 / EC:DMC. Furthermore, 10 volume% of vinylene carbonate (VC) was added to the 100 volume% solution to prepare an electrolyte for a lithium-sulfur secondary battery.
[0155] Comparative Example 6 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 11, except that the electrolyte solution was prepared as follows.
[0156] In the electrolyte, a mixed solvent of FEC and HFE mixed in a volume ratio of 50:50 was used as a non-aqueous solvent. LiTFSI was then dissolved in the mixed solvent to prepare a solution of 1.0 mol / L LiTFSI / FEC:HFE. Vinylene carbonate (VC) was then added at 10 volume% to the 100 volume% solution to prepare an electrolyte for a lithium-sulfur secondary battery.
[0157] 〔result〕 FIG. 1 is a graph showing the results of a charge-discharge test of the lithium-sulfur secondary batteries prepared in Example 1 and Comparative Examples 1 and 2.
[0158] From FIG. 1, it can be seen that the lithium-sulfur secondary batteries prepared in Example 1 and Comparative Example 2 could be charged and discharged more than 100 times, whereas the lithium-sulfur secondary battery prepared in Comparative Example 1 could only exhibit the discharge characteristics of the first cycle and could not be recharged.
[0159] Ethylene carbonate (EC) cannot penetrate into the micropores (pore diameter less than 2 nm) of activated carbon, but can penetrate into the mesopores. As described above, the ratio of the number of pores in the activated carbon used in Example 1, Comparative Example 1, and Comparative Example 2 was macropores:mesopores:micropores=0:40:60. The result of Comparative Example 1 is considered to be due to the fact that the EC, which is a solvent, penetrates into the mesopores, causing sulfur to dissolve as lithium polysulfide, and current generation ceased.
[0160] 1, it can be seen that a characteristic discharge occurs at around 1.8 to 2.3 V in the first cycle in Example 1 and Comparative Example 1. This shows that a coating is formed in the pores of the sulfur-loaded activated carbon in the positive electrode.
[0161] It is believed that the lithium-sulfur secondary batteries prepared in Example 1 and Comparative Example 2 were able to perform charge / discharge cycles of 100 or more, unlike Comparative Example 1, because the formation of the coating film prevented the solvent from entering the pores.
[0162] On the other hand, it is found that the lithium-sulfur secondary battery prepared in Example 1 has a much smaller polarization in the charge / discharge characteristics than the lithium-sulfur secondary battery prepared in Comparative Example 2. That is, it was revealed that the resistance of the lithium-sulfur secondary battery can be significantly reduced by using ClEC as a solvent for the electrolyte compared to the case where FEC is used.
[0163] Therefore, it can be said that the lithium-sulfur secondary battery prepared in Example 1 exhibits better charge-discharge characteristics than the lithium-sulfur secondary battery prepared in Comparative Example 1.
[0164] FIG. 2 and Table 1 show the results of the lithium-sulfur secondary batteries prepared in Example 1 and Comparative Examples 1 and 2 subjected to the above-mentioned cycle characteristic test.
[0165] [Table 1]
[0166] 2 and Table 1, the lithium-sulfur secondary battery prepared in Comparative Example 1 could not operate. As described above, this result is believed to be due to the fact that EC used as the solvent of the electrolyte penetrated into the mesopores and sulfur was dissolved out as lithium polysulfide.
[0167] The lithium-sulfur secondary battery prepared in Example 1 exhibited a higher discharge capacity in the second cycle than the lithium-sulfur secondary battery prepared in Comparative Example 2, and also exhibited higher capacity retention rate and average coulombic efficiency.
[0168] Furthermore, FIG. 2 shows that the lithium-sulfur secondary battery prepared in Example 1 exhibits a higher discharge capacity than the lithium-sulfur secondary battery prepared in Comparative Example 2 even when the number of cycles is increased, and the difference becomes larger as the number of cycles increases.
[0169] That is, it is found that the use of ClEC as a solvent for the electrolyte can improve the discharge capacity of a lithium-sulfur secondary battery more than the use of EC or FEC as the solvent.
[0170] 3 shows the results of a cycle characteristic test of the lithium-sulfur secondary batteries prepared in Example 2 and Comparative Examples 3 and 4. Table 2 shows the results of measuring the discharge capacity at the second cycle of the lithium-sulfur secondary batteries prepared in Examples 2 and 3 and Comparative Examples 3 and 4.
[0171] [Table 2]
[0172] As shown in FIG. 3 and Table 2, the lithium-sulfur secondary battery prepared in Comparative Example 3 was able to operate for up to 20 cycles, but the discharge capacity was low and it short-circuited after the 20th cycle and could no longer operate.
[0173] The lithium-sulfur secondary battery prepared in Comparative Example 3 uses EC as a solvent for the electrolyte, but has a higher ratio of micropores to the total pores of the activated carbon used than the lithium-sulfur secondary battery prepared in Comparative Example 1. In other words, the ratio of activated carbon into which EC cannot penetrate is high. Therefore, unlike the lithium-sulfur secondary battery prepared in Comparative Example 1, it is believed that the battery was able to operate for up to 20 cycles.
[0174] However, in the lithium-sulfur secondary battery prepared in Comparative Example 3, it is believed that the EC penetrated into the mesopores, causing the sulfur supported in the mesopores to dissolve, resulting in a short circuit after the 20th cycle.
[0175] It can be seen from Table 2 that the lithium-sulfur secondary batteries prepared in Examples 2 and 3 have a higher discharge capacity at the second cycle than the lithium-sulfur secondary batteries prepared in Comparative Examples 3 and 4. It can also be seen from FIG. 3 that the lithium-sulfur secondary battery prepared in Example 2 exhibits a higher discharge capacity than the lithium-sulfur secondary batteries prepared in Comparative Examples 3 and 4, even when the number of cycles is increased.
[0176] It is believed that the lithium-sulfur secondary batteries prepared in Examples 2 and 3 were able to retain a large amount of sulfur in the mesopores due to the use of ClEC as a solvent for the electrolyte. Therefore, it is believed that the lithium-sulfur secondary batteries prepared in Examples 2 and 3 were able to exhibit excellent discharge capacity, unlike the lithium-sulfur secondary battery prepared in Comparative Example 3.
[0177] In addition, as described above, the use of ClEC as the solvent can reduce the polarization of the charge-discharge characteristics compared to the use of FEC instead of ClEC as the solvent. This is believed to be the reason why the lithium-sulfur secondary battery prepared in Example 2 exhibited a higher discharge capacity than the lithium-sulfur secondary battery prepared in Comparative Example 4.
[0178] As shown in Example 3, the lithium-sulfur secondary battery using ClEC and FEC in combination as the solvent had a better second cycle discharge capacity than the lithium-sulfur secondary battery prepared in Comparative Example 4 that did not use ClEC as a solvent. This also shows the usefulness of using ClEC as the solvent.
[0179] Table 3 shows the results of the cycle characteristic test of the lithium-sulfur secondary batteries prepared in Examples 2, 4 and 5.
[0180] [Table 3]
[0181] As shown in Example 5 of Table 3, it was found that even when ClEC was used alone as the solvent for the electrolyte, the lithium-sulfur secondary battery exhibited a high discharge capacity.
[0182] Table 4 and FIG. 4 show the results of the cycle characteristic test performed on the lithium-sulfur secondary batteries prepared in Examples 6 to 10.
[0183] [Table 4]
[0184] As shown in Table 4 and Fig. 4, all of the lithium-sulfur secondary batteries prepared in Examples 6 to 10 exhibited high discharge capacities. As shown in Example 10, it was found that the lithium-sulfur secondary batteries exhibited high discharge capacities even when the proportion of ClEC in the electrolyte solvent was 30 volume % or less (the volume ratio of ClEC to HFE to VC was 30:70:10).
[0185] In other words, the ClEC content in the solvent in the electrolyte does not necessarily need to be higher than that of the co-solvent, and it can be said that a high discharge capacity can be obtained with a low ClEC content.
[0186] Table 5 shows the results of the cycle characteristic test for Examples 11 to 18 and Comparative Examples 5 and 6, that is, the discharge capacities at the second and fifth cycles and the capacity retention rates.
[0187] [Table 5]
[0188] As can be seen from Table 5, the second cycle discharge capacity of the lithium-sulfur secondary batteries prepared in all of the Examples was significantly higher than that of the lithium-sulfur secondary battery prepared in Comparative Example 5. That is, it was found that even when applied to a laminate cell, the discharge capacity can be significantly improved by using ClEC as a solvent for the electrolyte compared to the case of using EC.
[0189] In addition, the second cycle discharge capacities of the lithium-sulfur secondary batteries prepared in Examples 11 to 14, 16, and 17 were significantly higher than that of the lithium-sulfur secondary battery prepared in Comparative Example 6. That is, even when applied to a laminate cell, it was found that the discharge capacity can be improved by using ClEC as a solvent for the electrolyte compared to the case of using FEC.
[0190] The second cycle discharge capacities of the lithium-sulfur secondary batteries prepared in Examples 15 and 18 were comparable to that of the lithium-sulfur secondary battery prepared in Comparative Example 6. However, in view of the results in Table 5, which show that the capacity retention rate (5th cycle discharge capacity / 2nd cycle discharge capacity×100) when ClEC was used as the electrolyte solvent was greater than that when FEC was used, it can be said that ClEC is useful as an electrolyte solvent.
[0191] From the above results, it is found that the electrolyte for the lithium-sulfur secondary battery according to one embodiment of the present invention can prevent sulfur from eluting from the activated carbon even when the activated carbon has a high ratio of mesopores among the pores, and therefore, it is clear that the electrolyte can impart excellent charge / discharge characteristics and cycle characteristics to the lithium-sulfur secondary battery. [Industrial Applicability]
[0192] The electrolyte for lithium-sulfur secondary batteries and the lithium-sulfur secondary batteries according to one embodiment of the present invention can be widely used in fields such as mobile terminal devices such as mobile phones and personal digital assistants (PDAs), small electronic devices such as notebook computers, video cameras and digital cameras, home appliances, transportation devices (vehicles) such as electric bicycles, electric automobiles (electric vehicles), hybrid automobiles and trains, power generation devices such as thermal power generation, wind power generation, hydroelectric power generation, nuclear power generation, geothermal power generation and solar power generation, and natural energy storage systems.
Claims
1. An electrolyte for a lithium-sulfur secondary battery, The lithium-sulfur secondary battery comprises a composite material of porous carbon and sulfur as a positive electrode material, The porous carbon includes pores having a pore size of 2 nm or more, a solvent for the electrolytic solution contains ethylene carbonate having a chloro group, and the content of the ethylene carbonate having a chloro group in the solvent is 20% by weight or more and 100% by weight or less; The solvent of the electrolyte may contain a co-solvent other than ethylene carbonate. Electrolyte for lithium-sulfur secondary batteries.
2. The total volume of the pores in the porous carbon is 0.4 cm 3 / g or more 2.0cm 3 The electrolyte for a lithium-sulfur secondary battery according to claim 1, wherein the electrolyte has a pH of 1.0-1.
5.
3. The total volume of the pores in the porous carbon is 0.9 cm 3 / g or more 2.0cm 3 The electrolyte for a lithium-sulfur secondary battery according to claim 2, wherein the electrolyte has a molecular weight of 1.0 to 1.0 kg / g or less.
4. 4. The electrolyte for a lithium-sulfur secondary battery according to claim 1, wherein the weight of sulfur supported in the pores of the porous carbon is 30% by weight or more and 90% by weight or less with respect to the total weight of the porous carbon and the sulfur.
5. 5. The electrolyte for a lithium-sulfur secondary battery according to claim 4, wherein the weight of the sulfur supported in the pores of the porous carbon is 50% by weight or more and 90% by weight or less with respect to the total weight of the porous carbon and the weight of the sulfur.
6. The electrolyte for a lithium-sulfur secondary battery according to any one of claims 1 to 5, wherein the ratio of the amount of pores having a pore diameter of 2 nm or more to the total amount of pores in the porous carbon is 5% or more and 100% or less.
7. The electrolyte for a lithium-sulfur secondary battery according to claim 6, wherein the proportion of pores having a pore diameter of 2 nm or more is 40% or more and 100% or less.
8. The electrolyte for a lithium-sulfur secondary battery according to any one of claims 1 to 7, wherein the content of ethylene carbonate having a chloro group in the solvent is 30% by weight or more and 100% by weight or less.
9. The electrolyte for a lithium-sulfur secondary battery according to any one of claims 1 to 8, wherein the solvent comprises at least one selected from vinylene carbonate, hydrofluoroether, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and fluoroethylene carbonate.
10. The electrolyte for a lithium-sulfur secondary battery according to any one of claims 1 to 9 is contained therein, A lithium-sulfur secondary battery using a composite material of porous carbon and sulfur as a positive electrode material, the porous carbon containing pores having a pore size of 2 nm or more.
Citation Information
Patent Citations
Sulfur-carbon material
JP2013118191A
Binder, electrode containing the same, and electrochemical device
JP2016100094A
Alkali metal-sulfur secondary battery including a protected sulfur cathode and method of manufacture
JP2020509540A
Positive active material for lithium sulfur battery, method for manufacturing the same, and lithium sulfur battery including the same
KR1020160078734A
Positive active material for lithium sulfur battery, method for manufacturing the same, and lithium sulfur battery including the same
KR1020160078821A